2014
DOI: 10.3171/2014.1.jns131264
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and predictors of 30-day readmission for patients discharged home after craniotomy for malignant supratentorial tumors in California (1995–2010)

Abstract: Using administrative data, this study demonstrates a baseline glioma surgery 30-day readmission rate of 13.2% in California for patients who are initially discharged home. This paper highlights the medical histories, perioperative complications, and patient demographic groups that are at an increased risk for readmission within 30 days of home discharge. An analysis of conditions present on readmission that were not present at the index surgical admission, such as infection and seizures, suggests that some rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
71
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(87 citation statements)
references
References 14 publications
11
71
1
1
Order By: Relevance
“…21,24 Other studies reporting on the neurosurgery of the spine show varying results as well. 5,6,25,31,32,36,38 Three studies investigated ASA physical status classification and found it to be significantly elevated in the readmitted group. 21,24,30 Previously, the increasing ASA score has been connected to increased mortality and worse outcomes for several surgical procedures by Wolters et al 39 Comorbid illnesses were also an effective predictor of readmission.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…21,24 Other studies reporting on the neurosurgery of the spine show varying results as well. 5,6,25,31,32,36,38 Three studies investigated ASA physical status classification and found it to be significantly elevated in the readmitted group. 21,24,30 Previously, the increasing ASA score has been connected to increased mortality and worse outcomes for several surgical procedures by Wolters et al 39 Comorbid illnesses were also an effective predictor of readmission.…”
mentioning
confidence: 99%
“…21,24,30 This conclusion is not at all surprising, as studies usually have shown a significant association between diabetes or hypertension and poor postoperative improvement for various procedures. 3,4,7,15,25,35 Diabetes and other comorbid conditions have also been noted as causes of a prolonged in-hospital stay, 4 explaining why Jansson et al 19 and Pugely et al 30 found extended LOS to be predictive of worse outcome.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…10 Indeed, there are some reports corroborating these findings and suggesting that steroids produce a hypercoagulable state in patients. 4,11,12 Since the landmark report of Galicich et al in 1961, high-dose corticosteroids are routinely administered to patients undergoing cranial surgery. 7,9 More recently, a renewed interest in the use of corticosteroids for both the medical treatment and perioperative medical treatment of chronic subdural hematoma (CSDH) has been sparked.…”
Section: Deep Venous Thrombosis and Pulmonary Embolismmentioning
confidence: 99%
“…In the study by Marcus et al, 4 which utilized a statewide database to examine readmissions after supratentorial tumor resection (n = 18,506), they found that seizure was a main cause of readmission based on readmission ICD-9 codes. Do the authors have enough confidence in the validity of seizure diagnoses in this kind of database to recommend targeted prospective intervention?…”
Section: Include When Citingmentioning
confidence: 99%